2021
DOI: 10.1002/aoc.6465
|View full text |Cite
|
Sign up to set email alerts
|

Co(II), Ni(II), Cu(II), and Zn(II) metal complexes of chalcone: Synthesis, characterization, thermal, antimicrobial, photocatalytic degradation of dye and molecular modeling studies

Abstract: A thiazole-based chalcone ligand and its bidentate Co(II), Ni(II), Cu(II), and Zn(II) complexes of general formula [M (DMTP) 2 ], (DMTP = (E)-3-(3,-4-dimethoxyphenyl)-1-(thiazol-2-yl)prop-2-en-1-one) have been synthesized.The compounds were characterized by elemental analyses, molar conductance, fourier-transform infrared (FTIR) spectra, 1 H NMR, 13 C NMR, mass, UV-Vis., magnetic susceptibility, and thermal and powder X-ray diffraction (XRD) techniques. Based on spectral data, tetrahedral geometry is assigned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…To investigate the influence of hydrogen peroxide on the photocatalytic decomposition rate, one drop of H 2 O 2 solution (30%) was added to the reaction mixtures. The following equation was used to determine the contaminant’s photodecomposition efficiency (η) η = ( C o C t C o ) × 100 where C o is the starting concentration and C t is the concentration at time ( t ) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the influence of hydrogen peroxide on the photocatalytic decomposition rate, one drop of H 2 O 2 solution (30%) was added to the reaction mixtures. The following equation was used to determine the contaminant’s photodecomposition efficiency (η) η = ( C o C t C o ) × 100 where C o is the starting concentration and C t is the concentration at time ( t ) …”
Section: Methodsmentioning
confidence: 99%
“…where C o is the starting concentration and C t is the concentration at time (t). 33 To study the kinetics of MO photocatalytic degradation by MPCs, the experimental data were described by the Langmuir−Hinshelwood model, as expressed in the following equation:…”
Section: ■ Introductionmentioning
confidence: 99%
“…The structure-activity relationship (SAR) revealed that the heterocyclic ring and conjugated keto group in chalcones play a crucial role in enhancing antimicrobial activity. The authors reported that substitution with an electron acceptor (bromide group) increased antimicrobial activity compared to chalcones substituted with an electron donor (methoxy group) [71].…”
Section: Copper Complexes With Bidentate Thiazole Ligandsmentioning
confidence: 99%
“…[25][26][27][28] Some reported metal complexes of chalcones also exhibit antihyperglycemic and antimicrobial activities. [29,30] The electrochemical properties of various chalcones have been demonstrated using a three-electrode cell system in the presence of anhydrous acetonitrile and tetrabutylammonium hexafluorophosphate electrolyte. [31][32][33] In addition, Slobodinyuk et al reported the electrochemical oxidation of series of asymmetric chalcones.…”
Section: Introductionmentioning
confidence: 99%